Effect of Doping Nickel Oxide and Hybrid Graphene Oxide on Electrochemistry Supercapacitor Characteristrics of Manganese Dioxide Thin Film - Le, Dai Duong; Bui, Thi Thanh Huyen; Hoang, Thi Bich Thuy (Old Journal, 2018)
Nanostructured thin films of manganese dioxide and manganese dioxide doped with nickel oxide and hybridized graphene oxide are synthesized by electrochemical chronopotentiometry method. Manganese dioxide has the highest specific capacitance of 349.93 F/g; charge-discharge stability remains 73.81% after 500 CV cycles. When doped with nickel oxide and hybridized graphene oxide, porosity of the material increases, therefore, the specific capacitance of the material increases. Manganese dioxide doped with nickel oxide exhibits a specific capacitance of 384.56 F/g. The composite film manganese dioxide / graphene oxide offers the highest specific capacitance of 412.55 F/g, the large porosity and high charge-discharge stability; maintain 82.23% of its initial specific capacitance after 500 CV cycles of the charge-discharge operation.